2023
DOI: 10.1111/ger.12685
|View full text |Cite
|
Sign up to set email alerts
|

Singapore dentists' attitudes toward dental care provision for older adults with disabilities

Abstract: ObjectivesThis study aimed to assess dentists' attitudes toward providing dental care for older adults with disabilities in Singapore and the factors influencing their willingness to provide care.BackgroundDentists face a rapidly ageing patient demographic. Practitioner unwillingness to circumvent the attending challenges of care provision prevents older adults from accessing the dental care necessary for better oral and systemic health. Previous studies have reported on dentists' attitudes toward caring for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Nonetheless, the shortage of dentists who are able to offer proper geriatric care is clearly a major issue. In a recent study, it was clarified that Singapore dentists were less willing, confident and involved in the care of older adults with disabilities, while dentists with training in Gerodontology were more willing to provide care 36 . Another qualitative study also reported that Singapore dentists addressed the necessity of expansion of education and training in Gerodontology for dentists to build dentists' confidence or to increase their motivation in managing the oral health needs of dependent older adults, which will contribute to increase the number of dentists who engage in NH setting 4 …”
Section: Preparedness Of Education In Gerodontology In Singaporementioning
confidence: 99%
“…Nonetheless, the shortage of dentists who are able to offer proper geriatric care is clearly a major issue. In a recent study, it was clarified that Singapore dentists were less willing, confident and involved in the care of older adults with disabilities, while dentists with training in Gerodontology were more willing to provide care 36 . Another qualitative study also reported that Singapore dentists addressed the necessity of expansion of education and training in Gerodontology for dentists to build dentists' confidence or to increase their motivation in managing the oral health needs of dependent older adults, which will contribute to increase the number of dentists who engage in NH setting 4 …”
Section: Preparedness Of Education In Gerodontology In Singaporementioning
confidence: 99%